Impact of photoperiod and soybean genotypes (E-genes) on the composition of root exudates, growth and biofilm formation of rhizosphere microbiota of soybean isogenic lines - Hlushach, D. V.; Avksentieva, O. O.; Kot, Y. G. (Regulatory Mechanisms in Biosystems, 2025)
The study is dedicated to analyzing the impact of photoperiod on the quantitative and qualitative composition of root exudates in Glycine max (L.) Merr. with varying photoperiod sensitivity, as well as their influence on the growth and biofilm formation of the soil bacteria Bradyrhizobium japonicum and Bacillus subtilis . Soybean near-isogenic lines (NILs) differing in the allelic state of photoperiod sensitivity genes ( E1–E3 ) were used. The p lants were grown for 14 days in a controlled environment chamber under two light conditions: a short day (9 hours) and a long day (16 hours). Root exudates were collected for biochemical analysis of carbohydrate, protein, amino acid, phenol, and flavonoid content, and to evaluate their effects on bacterial growth and biofilm formation. The results demonstrate that the photoperiod significantly affects the composition of root exudates, with the effect depending on the allelic state of the E genes in the plant genotype. Under short-day conditions, short-day lines (Clark and L80-5879) and the day-neutral line L63-3117 exhibited an increase in monosaccharide content. In root exudates of all lines, short days led to a decrease in soluble protein content, and in lines with dominant E1–E3 genes, a reduction in amino acid content was observed. An exception was the day-neutral line L71-920 ( e1e2e3 ), in which amino acid content increased under short-day conditions. Short days significantly increased phenol content in the exudates of L63-3117 but decreased it in L71-920. In lines with the dominant E3 gene (Clark and L63-3117), short days led to an increase in flavonoid content, while in other lines it decreased. R oot exudates of the cv. Clark under short-day conditions inhibited the growth of B. japonicum , likely due to reduced amino acid and protein content, which serve as nitrogen sources, and an increase in flavonoids, which may exert an inhibitory effect. Exudates from line L80-5879 did not affect rhizobial growth, while those from L63-3117 inhibited it, likely due to low amino acid content. In contrast, exudates of L71-920 under short days stimulated rhizobial growth, which correlated with increased amino acid content, potentially acting as chemoattractants. Biofilm formation by Br. japonicum was suppressed by exudates of short-day lines regardless of photoperiod, whereas in day-neutral lines (L63-3117 and L71-920), short-day conditions significantly stimulated biofilm formation. For B. subtilis , exudates of all lines under long-day conditions inhibited biofilm formation, but under short days, lines with dominant E1–E3 genes promoted it, likely due to increased monosaccharide content as a carbon source. In co-cultivation of rhizobia and bacilli, exudates from most lines under short days enhanced biofilm formation, except in L71-920, where a decrease in monosaccharide content was observed. These results highlight the importance of gen o typic photoperiod sensitivity in forming the composition of root exudates and their influence on the rhizosphere microbiota in response to photoperiod. This has important implications for understanding the mechanisms regulating symbiotic interactions between soybean and microorganisms, and for optimizing agronomic practices for soybean cultivation across different latitudes.